Melatonin improves spermatogonial stem cells transplantation efficiency in azoospermic mice - Gholami, Mohammadreza (Mashhad University of Medical Sciences, 2014)
Objective(s): Transplantation quality improvement and reduction of cellular damage are important goals that are now considered by researchers. Melatonin is secreted from the pineal gland and some organs such as testes. According to beneficial effects of melatonin (such as its antioxidant and antiapoptotic properties), researchers have proposed that the use of melatonin may improve transplantation quality. The aim of this study was to investigate the effects of melatonin on the spermatogonial stem cells transplantation in the azoospermic mice. Materials and Methods: The testes of the BALB/c mice pups (6-day-old) after vitrified-thawed, were digested with enzymes (collagenase, DNaseΙ, trypsin-EDTA) to disperse the cells. The SSCs, type A, were isolated from the rest of testicular cells by MACS. Spermatogonial stem cells were labeled with PKH26 fluorescent kit. Labeled spermatogonial stem cells were transplanted into the testes of infertile mice (busulfan 40 mg/kg). The mice died two months after transplantation and the efficiency of spermatogenesis was investigated. TNP2 and hematoxyline-eosin staining were used to detect the efficiency of cell transplantation. Results: TNP2 were detected in the samples that received melatonin and spermatogonial stem cells transplantation, simultaneously. TNP2 was not detectable in the transplant recipient mice that received placebo for 10 weeks (control group). According to hematoxyline-eosin staining, melatonin improved structure of testes. Conclusion: Administration of melatonin (20 mg/kg) simultaneously with transplantation of spermatogonial stem cells in azoospermia mouse testis increases the efficiency of transplantation and improves structural properties of the testes tissue.